PENGARUH GAYA KEPEMIMPINAN DAN SUPERVISI TERHADAP KINERJA GURU DI SDN 1 TALANG KELAPA KABUPATEN BANYUASIN - Amrillah Azrin (Fakultas Ekonomi Universitas Tridinanti Palembang, 2014)
This study aimed to influence the style of leadership and supervision on the performance of teachers, From the results of this study are the influence of leadership style and Supervision of the performance of teachers at Palm Elementary School District 1 Gutters Banyuasin. Obtained a correlation coefficient (R) of 0.879, the value of determination coefficient of 0.772 or 77.2%. Regression coefficient of 0.625 and 0.489 so that the form of Multiple Regression equation is Y = 11.201 + 0.625 + 0.489 X1 + X2 e. There is the influence of leadership style on performance The correlation between variables Leadership Style (X1) with variable performance (Y) obtained values of 0.842 and R values of determination coefficient of 0.709 or 70.9%, and there is the influence of Supervision on Teacher Performance. Supervision of the correlation between variables (X2) with variable performance (Y) obtained R value of 0.746 and the coefficient of determination of 0.556 or 55.6%. Its implementation is an effort to improve the style of leadership ability to influence a group to achieve a particular goal or leadership in general is defined as activities to influence the behavior of others and an effort to increase development assistance and supervision is provided to improve and develop teaching and learning situation towards a better . Keywords: Performance, Leadership Styles and Supervision